EFFECT OF DIFFERENT HYBRIDS, SPACING AND FERTILIZER DOSES ALONG WITH THEIR INTERACTION (2 WAY) ON GROWTH AND YIELD OF BROCCOLI (Brassica oleracea var. italica L.) (International Journal of Environmental Sciences, 2025)
The present study was conducted to evaluate the effect of different hybrids, spacing and fertilizer doses along with their interaction (2 way) on growth and yield of broccoli (Brassica oleracea var. italica L.) at Department of Horticulture, Eternal University, Baru Sahib (Sirmaur). The experiment was conducted using a Factorial Randomized Block Design with three replications. The research trial consisted of three different hybrids (Saki, Diana, Besty), three spacings levels (60 × 30 cm, 60 × 45 cm and 60 × 60 cm) and three different fertilizer doses (75% RDF, 100% RDF, 125% RDF). The experimental results revealed that hybrid, spacing, fertilizer and their interaction showed significant effect on the vegetative characters and yield of broccoli. Among different hybrid, H3 (besty) recorded maximum plant height, plant spread, leaf area, stem girth and stem diameter. Whereas, number of leaves per plant and curd yield/m2 found under hybrid H2 (diana). In case of spacing levels, maximum plant height and curd yield/m2 was observed under spacing S1 (60 × 30 cm). Whereas, S3 (60 × 60 cm) recorded maximum plant spread, number of leaves per plant, leaf area, stem girth and stem diameter. Among different fertilizer doses, maximum value of all vegetative and yield parameters was found from the highest dose of fertilizer F3 (125% RDF) in both the years and pooled data. In respect of F×H interaction maximum plant height, plant spread, leaf area, stem girth and stem diameter were found under F3H3. Whereas, F3H2 recorded highest number of leaves per plant and curd yield/m2. For F×S interaction maximum plant spread, number of leaves per plant, leaf area, stem girth and stem diameter were found under F3S3. Whereas, F3S1 recorded highest plant height and curd yield/m2. In case of H×S interaction, H3S1 recorded highest plant height, curd yield/m2 was recorded highest under H2S1 and maximum number of leaves per plant was found under H2S3. Whereas, maximum plant spread, leaf area, stem girth and stem diameter were obtained from the treatment combinations H3S3.